Encyclopedia of Analytical Chemistry 2017
DOI: 10.1002/9780470027318.a6803.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Portable Systems for Energy‐Dispersive X ‐Ray Fluorescence Analysis

Abstract: Portable energy‐dispersive X‐ray fluorescence (EDXRF) spectrometers are very useful and popular in many fields for the on‐site analysis of elements because EDXRF is a nondestructive, multielemental, and inexpensive technique that is extremely well suited for the analysis of inorganic materials. An EDXRF spectrometer mainly consists of an X‐ or γ‐ray excitation source, an X‐ray detector with electronics, and a pulse‐height analyzer. Recent technological developments have resulted in small, low‐power, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Динамичное развитие характерно для детекторов с термоэлектрическим охлаждением [11,15,16], РФА с полным внешним отражением (РФА с ПВО) [11,15,[17][18][19][20][21][22] и с поляризацией излучения [23][24][25][26][27][28]. При исследовании разнообразных биологических материалов широко применяются удобные портативные энергодисперсионные рентгенофлуоресцентные (ЭДРФА) спектрометры ряда фирм [29][30][31]. Конструирование и массовое производство портативных спектрометров стало возможным после усовершенствования детекторов с термоэлектрическим охлаждением: кремний дрейфовых детекторов (silicon drift detectors , SDD) и PIN диодов и решением технологических проблем, связанных с выпуском небольших маломощных рентгеновских трубок с воздушным охлаждением [11,32].…”
Section: аппаратураunclassified
“…Динамичное развитие характерно для детекторов с термоэлектрическим охлаждением [11,15,16], РФА с полным внешним отражением (РФА с ПВО) [11,15,[17][18][19][20][21][22] и с поляризацией излучения [23][24][25][26][27][28]. При исследовании разнообразных биологических материалов широко применяются удобные портативные энергодисперсионные рентгенофлуоресцентные (ЭДРФА) спектрометры ряда фирм [29][30][31]. Конструирование и массовое производство портативных спектрометров стало возможным после усовершенствования детекторов с термоэлектрическим охлаждением: кремний дрейфовых детекторов (silicon drift detectors , SDD) и PIN диодов и решением технологических проблем, связанных с выпуском небольших маломощных рентгеновских трубок с воздушным охлаждением [11,32].…”
Section: аппаратураunclassified
“…In the last decades, a huge increase of the methodologies and techniques in chemistry to support the studies of the archeologists was observed. Cultural heritage objects can be unique and irreplaceable, and every time, the approach needs to be adapted to the specific case study. The best practices in this field should follow a Standard Operating Procedure (SOP), which plan the use of the techniques of analysis as a function of the goal of the investigation. The SOP provides the necessary guidance because a multianalytical noninvasive and microinvasive approach to a work of art implies a number of tasks with a strict order of compilation, which is strictly related the kind of information that is possible to gather from each analysis.…”
Section: Introductionmentioning
confidence: 99%